Parent-offspring regression analysis for total carotenoids and some agronomic traits in cassava. - Njoku, D.; Gracen, V.; Offei, S.; Asante, I.; Egesi, C.; Kulakow, P.; Ceballos, H. (Euphytica, 2015)
Six cassava cultivars, three yellow and three white-fleshed roots were crossed in a 3 × 3 topcross mating design to generate nine F1 populations. One thousand, one hundred and ten botanical seeds from the 9 populations were sown in pots and maintained for 42 days in a screenhouse. The emerged seedlings were transplanted to the field in April, 2010 alongside their parents (from stem cuttings), family by family. Four hundred and sixty-four progenies survived and were harvested. Both field and laboratory data were used to evaluate total carotene content (TCC), dry matter content (DMC), storage fresh root yield (SFRY) and other root quality traits. Seed germination for different populations ranged between 15.5 and 80.9 % with a mean of 43.19 %. Phenotypic variation in DMC, TCC, SFRY, biomass, root number, harvest index and cassava mosaic disease (CMD) were recorded in all the families. Average values for the populations were TCC: 4.59 μg g−1, DMC, 33.58 % and SFRY, 18.42 t ha−1. Narrow sense heritability by midparent-offspring regression analysis and genetic gains were estimated for TCC, DMC, SFRY and reaction to CMD. TCC, DMC and CMD gave high heritability estimates of 0.73, 0.83 and 0.84, respectively. SFRY, on the other hand, had a low heritability estimate (0.15). TCC was negatively correlated with DMC across all evaluation stages and locations. There were very high levels of variation in the segregating F1 progenies for all the traits. Also, narrow sense heritability estimate showed that genetic factors played a more important role than environmental factors for TCC, DMC and CMD, suggesting that reliable selection with simple recurrent phenotypic selection would be rewarding.
Keywords: Carotenoid; Botany; Biology; Offspring; Regression analysis; Heritability; Mating design